2023
DOI: 10.3390/foods12213901
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Potential of Sprouted Cereals, Pseudocereals, and Pulses in Combating Malnutrition

Mahsa Majzoobi,
Ziyu Wang,
Shahla Teimouri
et al.

Abstract: Due to the global rise in food insecurity, micronutrient deficiency, and diet-related health issues, the United Nations (UN) has called for action to eradicate hunger and malnutrition. Grains are the staple food worldwide; hence, improving their nutritional quality can certainly be an appropriate approach to mitigate malnutrition. This review article aims to collect recent information on developing nutrient-dense grains using a sustainable and natural process known as “sprouting or germination” and to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
1
6
0
Order By: Relevance
“…The course of these transformations in the grain depends on the conditions of the malting process, such as the degree of humidity, temperature, and time of germination, as well as kilning parameters [4,22,23,52]. Majzoobi et al [15] reported that different components of the same grain may vary differently or remain unchanged under similar germination conditions. According to the authors, the protein content in sprouted grains depends on the balance between protein breakdown and its biosynthesis during germination.…”
Section: Chemical and Color Characteristics Of Quality Of Baking Floursmentioning
confidence: 99%
See 2 more Smart Citations
“…The course of these transformations in the grain depends on the conditions of the malting process, such as the degree of humidity, temperature, and time of germination, as well as kilning parameters [4,22,23,52]. Majzoobi et al [15] reported that different components of the same grain may vary differently or remain unchanged under similar germination conditions. According to the authors, the protein content in sprouted grains depends on the balance between protein breakdown and its biosynthesis during germination.…”
Section: Chemical and Color Characteristics Of Quality Of Baking Floursmentioning
confidence: 99%
“…Redaelli et al [75] reported that the total beta-glucan content in the assessed European oat genotypes ranged from 2.85 to 6.77% d.m., and the soluble fraction from 2.05 to 5.29% d.m., which constituted 50.7-87.0% of their total content. During the malting process, the beta-glucan present in the grain is broken down by cytolytic enzymes (mainly beta-glucanases) [15,22,23]. Hübner et al [52] observed a decrease in the beta-glucan and the S-DF contents in oat malt as the germination time was extended and the germination temperature was increased.…”
Section: Characteristics Of Nutritional Value and Antioxidant Potenti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The germination process of pseudocereal grains not only enhances the concentration and accessibility of nutrients [5][6][7], but also diminishes the presence of antinutritional factors [8,9]. This transformative process has been associated with heightened levels of bioactive compounds, including phenolic compounds, γ-aminobutyric acid, and increased antioxidant activity [10][11][12]. Beyond nutritional considerations, the flavor and texture of sprouted grains are expected to vary due to processing conditions and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Germination of different grains is triggered by specific conditions, including optimal temperature, light, and moisture to support plant growth. Suitable germination conditions activate the relevant enzymes and hormones, transforming the grain from dormancy to active metabolism and facilitating the release of nutrients [ 8 ]. Products based on germinated grains represent new components in the food industry that have enhanced nutritional value, mineral absorption, flavor, and taste [ 9 ].…”
Section: Introductionmentioning
confidence: 99%